Symbolic naratives of the fourth gospel the interplay of form and meaining - Lee, Dorothy A. (Sheffield, UK Sheffield Academic, 1994)
Includes bibliographical references and indexes.
Based on PhD thesis, University of Sydney, Department of Religious Studies, July 1991.
Keywords: Bible. N.T. John -- criticism, interpretation, etc